The use and effect of concept mapping heuristic in facilitating learning of varying ability groups in college introductory biology - San Juan, Asuncion V. (Animo Repository, 1990)
This study undertakes to determine whether concept mapping as a method in teaching biology is effective in facilitating learning in terms of better performance in achievement test. The pretest-posttest non-equivalent control group design was used in this study with a teacher-made test as the sole instrument in gathering data. Three biology classes, a total of 98 college students, were used as the subjects of the study. One class formed the control group and was taught by the traditional lecture method. The other two classes formed the experimental group and one of them was taught by the concept method while the other one was taught by combined concept mapping and lecture method. Analysis of covariance was used to analyze the data. T-test for correlated samples was applied in the analysis of students' retention on biology concepts. This study showed that students taught by concept mapping method performed comparable with those taught by combined concept mapping and lecture method but significantly outscored those taught by the traditional lecture method. The retention knowledge of students exposed to concept mapping method was more efficient than those exposed to lecture method. The effect of teaching method on students' achievement scores is independent of the type of student. Thus, concept mapping method is effective in learning biology and it also helps improve the retention power of students on biology concepts.